Combustion behavior and mechanical properties of pellets derived from blends of animal manure and lignocellulosic biomass. (15th July 2021) - Wzorek, Małgorzata; Junga, Robert; Yilmaz, Ersel; Niemiec, Patrycja
Abstract: This paper presents the possibility of valorization of animal manure (camel and cow) by mixing it with agro-industrial biomass (cotton stalk and rapeseed oil cake) to produce pellets for use in power generation processes. Feedstocks were mixed in specific proportions based on certain assumptions concerning the energy and mechanical parameters of pellets. The assessment concerned both the combustion behavior as well as mechanical properties of four types of pellets derived from blends of animal manure and agro-industrial biomass. Thermogravimetry (TGA) and Differential Scanning Calorimetry (DSC) techniques are applied to analyze the reaction areas, characteristic temperatures as well as heat flow rates of raw materials and their blends. Results showed that addition of agro-industrial biomass (even 10%) to animal manure changed the specific combustion parameters: initiation and burn-out temperature and combustion time. For blends of cow manure (COM) and rapeseed oil cake (ROC), a reduction in the initiation temperature was achieved compared to the combustion of raw cow manure, and the combustion time increased by 1/3. In the case of camel manure (CAM) with the addition of cotton stalk (CS) the burn-out temperature and combustion time decreased. The addition of agro-biomass also causes a change in the heat release profiles, for the blends no pronounced DSC peaks are obtained in the area of devolatilization as it happens animal manure alone and in the area of fixed carbon combustion as for cotton stalk and rapeseed oil cake. The heat released from camel manure blends was 9.2–9.3 kJ/kg and from cow manure blends 10.2–10.4 kJ/kg. An evaluation of the physical and mechanical properties showed that all types of pellets at a moisture content of 10–15% have a similar drop strength in the range of 80–85%, while this strength decreases to 40–60% after the pellets have absorbed water. Graphical abstract: Image 1 Highlights: Pellets from animal manure with addition of ago-industrial biomass were developed. Addition of agro-industrial biomass (even 10%) changed the main combustion parameters. The heat released from the blends was in the range of 9.2–10.4 kJ/kg. 10–15% moisture content of pellets determines their stability and durability. Drop strength for the pellets was all above 80%.